Metodología práctica para la cuantificación de la huella de agua en Plantas Empacadoras de banano en Costa Rica - Vallejo-Chaverri, Ana Lorena (Instituto Tecnológico de Costa Rica, 2015)
There is currently great pressure on water resources worldwide; therefore, the efforts should be focused towards development that includes the integrated management of this resource. The Costa Rican banana sector as a user of water, requires practical and accessible tools to promote the efficient and appropriate use of this resource in the packing plants facilities. For this purpose, a methodology to quantify the scarcity and eutrophication water footprint was proposed. For its developing, a comprehensive literature review of available methods for measuring the footprint was made, comparative tables of these were built, the suitable methods for the sector were selected and the proposed guide was evaluated in a practical case. The ISO 14046:2014 was selected as the basis for the development of the methodology, in which the environmental impacts evaluated were eutrophication by following ReCiPe’s method, and scarcity, human health, ecosystem quality and resources, by Pfister’s et al. (2009) method. The proposal, guides the reader through visual aids and practical examples to calculate the scarcity and eutrophication water footprint because of its direct use in the banana packing plants. In the implementation in San Pablo´s farm of CORBANA, it was possible to identify improvement opportunities important for the efficient management of the resource, which is the main benefit of its application. The synthesis and facilitated access to this complex indicator, is the most important contribution of this project to the Costa Rican banana industry.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental). Instituto Tecnológico de Costa Rica. Escuela de Química, 2015.
Keywords: Utilización del agua; Empacadoras; Procedimiento; Impacto ambiental; Metodología de análisis; Ecología y desarrollo